2020
DOI: 10.1002/adfm.202005136
|View full text |Cite
|
Sign up to set email alerts
|

Bioinspired Molecular Bridging in a Hybrid Perovskite Leads to Enhanced Stability and Tunable Properties

Abstract: Hybrid perovskites demonstrate high potential in optoelectronic applications. Their main drawback is their low stability under humid conditions. In this paper, one of nature's strategies is implemented-the incorporation of amino acids into the crystal lattice-in order to improve the stability of methylammonium lead bromide (MAPbBr 3) in water, and to tune its structure, as well as its optical and thermal properties. The amino acid lysine, which possesses two NH 3 + groups, is incorporated into the hybrid unit … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 98 publications
3
18
0
Order By: Relevance
“…The findings of this research validate the bioinspired route of band engineering via incorporation of AAs into NIR semiconductors. This study also further generalizes the bioinspired band gap engineering phenomenon for UV (ZnO [19,20] ), Vis (Cu 2 O [21] and MAPbBr 3 [22] ), and IR (PbS, this work) optical band gaps.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…The findings of this research validate the bioinspired route of band engineering via incorporation of AAs into NIR semiconductors. This study also further generalizes the bioinspired band gap engineering phenomenon for UV (ZnO [19,20] ), Vis (Cu 2 O [21] and MAPbBr 3 [22] ), and IR (PbS, this work) optical band gaps.…”
Section: Discussionsupporting
confidence: 68%
“…The observation of the band gap widening in the case of a semiconductor with a band gap in NIR range is a further corroboration of the bioinspired route to effectively tune the band gap of semiconductors, [ 23 ] and extends its validity to the IR regime. Moreover, here yet again the band gap is blueshifted as in all the other cases studied previoiusly, [ 19–23 ] and redshifted back after a mild annealing (Figure S2, Supporting Information). [ 19,21 ] These shifts strengthen the notion that the mechanism by which the incorporated AAs tune the hosts’ band gap is at least partly via quantum size effects due to the confinement of electrons and holes in between adjacent AAs in the host lattice.…”
Section: Resultsmentioning
confidence: 58%
“…The champion device with n:8 showed PCEs of 18.05%, V OC s of 1.08 V, and J SC s of 22.9 mA cm −2 (Table 2). Another interesting effect was recently reported by Lang et al [374] The researchers investigated the effect of the amino acid l-lysine during the perovskite formation. While a comparable behavior was noticed, the authors also reported that amino acid additives strongly increase the perovskite stability in water.…”
Section: Sensitizermentioning
confidence: 84%
“…Incorporation of amino acids in calcite (CaCO 3 ) enhances the hardness of the hybrid crystals, 2 while improved stability and increase in band gap are achieved for organometal halide perovskites and ZnO crystals. 8 10 The occlusion of functional nanoparticles is particularly attractive, as their properties can be predefined using well-established synthetic methods. For example, the incorporation of metal oxide nanoparticles 11 13 in KH 2 PO 4 and K 2 SO 4 has created single crystals for optoelectronic and photonic devices, while calcite-containing polymer nano-objects 14 and magnetic nanoparticles 15 exhibit enhanced physical properties.…”
Section: Introductionmentioning
confidence: 99%